1999
DOI: 10.1177/089686089901900307
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Solution and Spent Dialysate Stimulate the Synthesis of Transforming Growth Factor-β1 of Human Peritoneal Mesothelial Cells: Effect of Cytokine Costimulation

Abstract: Objective To investigate the effect of high glucose and spent peritoneal dialysate on the transforming growth factor-β1 (TGFβ1) synthesis of cultured human peritoneal mesothelial cells (HPMCs) and to examine the effect of costimulation with high glucose or spent dialysate, and cytokines, interleukin-1β (IL-1β), and tumor necrosis factor-α (TNFα) on TGFβ1 synthesis of HPMCs. Design HPMCs were exposed to different concentrations of glucose (30, 60, and 90 mmol/L) or spent peritoneal dialysate for 48 hours in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(66 citation statements)
references
References 34 publications
3
62
0
1
Order By: Relevance
“…Chronic exposure of the rat peritoneal membrane to a high-glucose conventional PDF resulted in mesothelial damage, submesothelial and interstitial fibrosis and neoangiogenesis. This result supports previous reports that in vitro exposure of endothelial and mesothelial cells to high glucose stimulates the expressions of VEGF (12) and TGF-β (13), and that chronic in vivo exposure of the peritoneal membrane to high glucose concentrations results in microvascular proliferation and submesothelial fibrosis, which are mediated by VEGF and TGF-β, respectively (14). Glucose degradation products are produced from glucose because of both heat sterilization and storage of PDF, and are known to be one of the bioincompatible factors of glucose-based dialysis solutions, which induce both functional and structural alterations of the peritoneum (7,15).…”
Section: Discussionsupporting
confidence: 92%
“…Chronic exposure of the rat peritoneal membrane to a high-glucose conventional PDF resulted in mesothelial damage, submesothelial and interstitial fibrosis and neoangiogenesis. This result supports previous reports that in vitro exposure of endothelial and mesothelial cells to high glucose stimulates the expressions of VEGF (12) and TGF-β (13), and that chronic in vivo exposure of the peritoneal membrane to high glucose concentrations results in microvascular proliferation and submesothelial fibrosis, which are mediated by VEGF and TGF-β, respectively (14). Glucose degradation products are produced from glucose because of both heat sterilization and storage of PDF, and are known to be one of the bioincompatible factors of glucose-based dialysis solutions, which induce both functional and structural alterations of the peritoneum (7,15).…”
Section: Discussionsupporting
confidence: 92%
“…Peritoneal mesothelial cells play an important role in the process of peritoneal fibrosis. Researches have suggested that peritoneal mesothelial cells can produce TGF-b with the stimulation of high concentration of sugar (Kang et al, 1999). TGF-b1, a cytokine with multiple function, can not only stimulate the synthesis of extracellular matrix, but also inhibit its degradation, therefore, it is the critical factor in the process of peritoneal fibrosis (Border and Noble, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that glucose induced damage to the peritoneal membrane is due not only to osmolality but also the polyol pathway. Kang et al (24) reported that glucose stimulates TGFb mRNA expression, while mannitol at the same osmolarity does not. Further study on the osmotic effects of glucose on PAI-1 mRNA expression is needed.…”
Section: Discussionmentioning
confidence: 99%